Post-operative pain following cardiac implantable electronic device implantation: insights from the BRUISE CONTROL trials. Issue 5 (28th December 2020) - Nair, Girish M; Birnie, David H; Sumner, Glen L; Krahn, Andrew D; Healey, Jeffrey S; Nery, Pablo B; Kalfon, Eli; Verma, Atul; Ayala-Paredes, Felix; Coutu, Benoit; Becker, Giuliano; Philippon, François; et al.
Abstract: Aims : Post-operative pain following cardiac implantable electronic device (CIED) insertion is associated with patient dissatisfaction, emotional distress, and emergency department visits. We sought to identify factors associated with post-operative pain and develop a prediction score for post-operative pain. Methods and results : All patients from the BRUISE CONTROL-1 and 2 trials were included in this analysis. A validated Visual Analogue Scale (VAS) was used to assess the severity of pain related to CIED implant procedures. Patients were asked to grade the most severe post-operative pain, average post-operative pain, and pain on the day of the first post-operative clinic. Multivariable regression analyses were performed to identify predictors of significant post-operative pain and to develop a pain-prediction score. A total of 1308 patients were included. Multivariable regression analysis found that the presence of post-operative clinically significant haematoma CSH; P value < 0.001; odds ratio (OR) 3.82 [95% confidence interval (CI): 2.37–6.16], de novo CIED implantation [ P value < 0.001; OR 1.90 (95% CI: 1.47–2.46)], female sex [ P value < 0.001; OR 1.61 (95% CI: 1.22–2.12)], younger age [<65 years; P value < 0.001; OR 1.54 (95% CI: 1.14–2.10)], and lower body mass index [<20 kg/m 2 ; P value < 0.05; OR 2.05 (95% CI: 0.98–4.28)] demonstrated strong and independent associations with increased post-operative pain. An 11-point post-operative pain prediction score was developed using the data. Conclusion : Our study has identified multiple predictors of post-operative pain after CIED insertion. We have developed a prediction score for post-operative pain that can be used to identify individuals at risk of experiencing significant post-operative pain.